NUTRITION KNOWLEDGE AND NUTRITIONAL PRACTICE OF PHYSICAL ACTIVITY TEACHERS IN PELOTAS, RS (Fiep Bulletin - online, 2014)
The present article aimed to investigate the nutrition knowledge and the nutritional practice of Physical Education teachers in gymnastic academies located in downtown Pelotas, Rio Grande do Sul, Brazil. The sample was constituted of 48 teachers, being 21 female and 27 male, aged between 21 and 50 years old. General data as well as nutrition-related knowledge were collected through a close-questionnaire. To evaluate nutritional consumption it was utilized the nutritional daily record of meals during three alternate days. The analysis of dietary adequacy was made with the utilization of the Dietwin software (2003 version). The results show that the professionals not only do not know the correct way of distributing macronutrients but also do not pay the proper attention concerning the ingestion of nutritional supplements. In general, the nutrition of female teachers showed to be hypocaloric, hyperproteic and hypolipidic while the nutrition of male teachers consisted of hyperproteic diets and ingestion of nutritional supplements. It was also verified the existence of misleading concepts both in relation to the description of a balanced diet and to the use of supplements without nutritional orientation.
Keywords: nutrition knowledge; nutritional practice; teachers; Physical Education